PELATIHAN PEMBUATAN BATIK SHIBORI BAGI PENGURUS DAERAH WANITA ISLAM KOTA SEMARANG - Heny Kusuma Yanti; Vita Paramita; Aulia Windyandari; Ida Hayu Dwimawanti; Rizka Amalia; Aprilia Larasati Dewi; Ida Rahmawati Cahyaningsih; Ilyas Teguh Pangestu (Jurnal Pengabdian Vokasi, 2020)
Community service training on making shibori batik for the regional Islamic board administrator of the city of Semarang ran smoothly. The trainees are interested and passionate in being able to make batik with various unique motifs using shibori techniques. In this training, making batik shibori by using tools and materials that are easily available. By making batik, the selling value of the fabric will increase, in addition to the results of shibori batik used by themselves can also be marketed so that it can improve the welfare of the community.